A new isoflavone from the roots of Ficus auriculata. Issue 1 (2nd January 2018) - Qi, Cui-Cui; Fu, Yan-Hui; Chen, Wen-Hao; Chen, Guang-Ying; Dai, Chun-Yan; Song, Xiao-Ping; Han, Chang-Ri
Abstract: A new isoflavone, 5, 7, 4′-trihydroxy-3′-hydroxymethylisoflavone (1 ), together with three known isoflavones, 3′-formyl-5, 4′-dihydroxy-7-methoxyisoflavone (2 ), ficuisoflavone (3 ) and alpinumisoflavone (4 ), were isolated from the roots of Ficus auriculata . Among them, 1 is a rare isoflavone containing 16 carbon atoms on the carbon skeleton. The structure of1 was elucidated by extensive spectroscopic methods and the known compounds were identified by comparisons with data reported in the literature. All compounds were evaluated for their antibacterial activities against five terrestrial pathogenic bacteria in vitro . Compounds1 –4 showed significant antibacterial activities against various terrestrial pathogenic bacteria with MIC values ranging from 1.30 to 39.93 μM. Abstract :